ДИЗАЙНЕРЛИК ФАОЛИЯТГА ОИД ИХТИСОСЛИК ФАНЛАРНИ АМАЛИЙ ЎҚИТИШ МЕТОДЛАРИ ЁРДАМИДА КАСБИЙ ТАЪЛИМНИ САМАРАЛИ ТАШКИЛ ЭТИШ - Дж.Тошева, Г. (SCIENCE and SOCIETY, 2021)
The goals and competencies of a teacher of vocational education, theoretical and methodological approaches, principles, structural components, stages of practical training, as well as the objective need to change the process of vocational and pedagogical training of teachers of vocational education, as well as in modern conditions, the analysis of interrelations and problems, allowing to overcome the contradictions between these that this problem has not been sufficiently worked out both in methodological and practical terms.